Historical Chaikhana – Dialogue of Uzbek Tea Culture (Eurasian Scientific Herald, 2022)
In the middle ages chaikhana – local teahouses was located next to the caravanserai and sardoba in the main cities of Central Asia, where they served green tea, sherbet and other soft drinks, as well as pilaf, fruits and other treats. Due to the high cost of tea, people went to special teahouses to drink and enjoy it. The chaikhana usually had light lattice walls and was located in the shade of trees, above the canal. The clients sat around the dastarkhan on carpets. They rested in the chaikhana, indulged in conversations and games.